From Paddock to Foal: Prevalence and Genotypic Diversity of Rhodococcus equi on Stud Farms in Türkiye - Yerlikaya, Zeynep; Karagulle, Burcu; Otlu, Baris; Muz, Adile (Mdpi, 2026)
Pneumonia caused by the facultative intracellular pathogen Rhodococcus equi stands out as one of the most significant infections associated with a notably high mortality rate in foals worldwide. Limited therapeutic options and inadequate control and prevention measures result in substantial economic losses, underscoring the need for enhanced interventions. A cross-sectional, multi-province study was conducted on racehorse-breeding farms in T & uuml;rkiye to estimate prevalence and index virulence, assess relatedness, and summarize antimicrobial susceptibility within a farm management context. Nasal and fecal swabs and environmental samples (soil and water) were cultured and confirmed; virulence was assessed with vapA-specific PCR, genetic relationship determined with PFGE, and antimicrobial susceptibility using disk diffusion. R. equi was detected in 10% of nasal swabs, 22.9% of fecal swabs, 29.4% of soil samples, and 5.9% of water samples; 46.2% of confirmed isolates were vapA-positive. Susceptibility patterns were favorable overall, with frequent ampicillin resistance, infrequent resistance to macrolides and rifampin, rare multidrug resistance, and no vancomycin resistance was detected. PFGE demonstrated substantial genotypic diversity, with 12 clusters and 29 distinct pulsotypes. Farm-level observations were exploratory. More frequent mechanical paddock cleaning coincided with the absence of foal deaths, and vapA-positive isolates were observed on farms with prior infection. Taken together, these findings support routine paddock hygiene, prompt isolation of clinically affected foals, culture-guided therapy, and continued surveillance, and they indicate a need for longitudinal and genomic studies to evaluate the impact.
Keywords: Rhodococcus equi; vapA; PFGE; PCR; antimicrobial resistance; foal pneumonia